Strategi pemasaran: Flash Sale dan Live Streaming terhadap keputusan pembelian impulsif pada platform e-commerce - Kapriani, Kapriani; Jusman, Ikhsan Amar; Marsuki, Marsuki (Jurnal Online Manajemen ELPEI, 2025)
The phenomenon of using flash sales and live streaming has increasingly dominated marketing strategies in the digital world, especially during the pandemic which has forced many activities to switch to online platforms. This study aims to explore more deeply the influence of these two factors on impulsive purchasing decisions on e-commerce platforms. The study population consisted of Shopee platform users in Makassar City, with a sample of 100 respondents selected using the non-probability sampling method. The results showed that partially and simultaneously, Flash Sale and Live Streaming have a significant effect on impulse buying decisions on e-commerce platforms.